2013
DOI: 10.1001/jamasurg.2013.1058
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Vascular Reconstruction During Pancreatectomy for Malignant Disease

Abstract: Objective: To assess trends in the frequency of concomitant vascular reconstructions (VRs) from 2000 through 2009 among patients who underwent pancreatectomy, as well as to compare the short-term outcomes between patients who underwent pancreatic resection with and without VR.Design: Single-center series have been conducted to evaluate the short-term and long-term outcomes of VR during pancreatic resection. However, its effectiveness from a population-based perspective is still unknown. Unadjusted, multivariab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Furthermore, there was an increase of resections of advanced malignancies which can be observed by an increase in portal vein resections. The latter was not associated with a higher morbidity in our collective, while larger studies show that venous resection is associated with increased morbidity rates [ 14 ].…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, there was an increase of resections of advanced malignancies which can be observed by an increase in portal vein resections. The latter was not associated with a higher morbidity in our collective, while larger studies show that venous resection is associated with increased morbidity rates [ 14 ].…”
Section: Discussionmentioning
confidence: 52%
“…While any SMPV occlusion and any arterial encasement had been considered a criterion of irresectability before, the ISGPS followed the National Comprehensive Cancer Network (NCCN) definition of borderline resectability and classified SMPV distortion and even short-segment venous occlusion-as well as the encasement of the gastroduodenal or hepatic artery and up to 180 • abutment of the SMA-as borderline resectable cases. Meta-analyses and large national cohort studies had shown higher rates of postoperative morbidity, but comparable rates of postoperative mortality and long-term overall survival after PVRs, as compared to patients without venous resections for PDAC [6,7]. In consequence, PVR was no longer considered an obstacle for curative resection if venous reconstruction was feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The Chi-square test was first used to explore whether or not NSCLC patients' participation in MDT care was related to their individual characteristics, including gender, age, urbanization level of the residence area, socioeconomic status (including premium-based monthly salary), health condition (including cancer stage, CCI), presence of other catastrophic injuries or illnesses besides cancer, and the annual service volume of the primary healthcare provider and the attending physician. The propensity score (PS), which has being widely adopted in many papers[ 9 , 23 , 24 ], was used in this study to balance the groups of MDT participants and MDT non-participants groups to reduce selection bias. It was the conditional probability of each MDT participants and its calculation was based on the variables that were listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%